Achieving food security in southern Africa: new challenges, new opportunities - Haddad, Lawrence James (International Food Policy Research Institute, 1997)
Until recently, civil strife, drought, and economic stagnation joined forces in Southern Africa to produce severe hunger and poverty. Now Southern Africa is experiencing a wave of economic and political reform that has the potential to raise living standards and bring the countries of the region into the world economy as full participants. The challenges are enormous, but so are the opportunities. Whether the countries of Southern Africa can make good on these opportunities depends on the steps policymakers take now. But a lack of resources often forces policymakers in the region to make decisions based on incomplete information and cursory analysis. This volume brings together experts from Southern Africa and elsewhere to consider food policy areas that suffer from especially limited information: macroeconomic and trade reform, smallholder agriculture, management of water resources, social security and safety net programs, and rural infrastructure. Managing these five areas wisely will go a long way toward helping Southern Africa embark on a path of increasing food security, equity, and economic growth.